Long term effect of a school based antismoking programme. Issue 3 (September 1984) - Murray, M; Swan, A V; Clarke, G
Abstract : In the winters of 1977-8 and 1978-9 about 400 children in seven junior schools in northern England were taught the "My Body" health education programme. In the springs of 1980 and of 1982 these children, and an age matched control group, answered a questionnaire about their smoking behaviour, knowledge, and attitudes. Comparison of the two groups suggested that the programme had had a positive effect on the boys but a negligible, or even negative, effect on the girls. Various suggestions as to the reasons for this differential impact are discussed.